(untitled) (Jurnal Teknologi (Sciences & Engineering), 2016)
Nowadays, lighting shares a large part in the global energy consumption, lighting consumption can be easily reduced with the use of efficient light sources. The most commonly used light source is the incandescent light bulb. As time passed by, Compact Fluorescent Lamp and Light Emitting Diode use became prevalent because of their advantages over the incandescent light. The researchers were able to develop and implement a PID controlled lighting system using Light Emitting Diode utilizing the smoothing-averaging technique in its sensors. Tests were done with the system with and without smoothing technique to identify the effect of the technique used. The system automatically varies its light intensity output depending on the light stimuli maintaining the luminance level of the laboratory based on standards.